HUKUM ISLAM DAN TOLERANSI TASAWUF ATAS BUDAYA - Fokky Fuad Wasitaatmadja (Jurnal Ilmiah Mimbar Demokrasi, 2017)
Research on Islamic law and sufism become important due to the fact that sufism is forbidden legally because it is receptive value outside of Islam. Some Islamic scholars allow so long as not to contradict the rules of Islamic law. Because it needs to be studied in depth interaction with the method of Islamic self-approach method of man to God in the epistemology of Islam. The problem formulation in this research is how tolerance values of sufism in cultural development process? Furthermore how is the interaction of sufism and sharia in the process of cultural approach? The method used in this research is sociological method, while the theory used is the cultural legal theory. Research results show that: Firstly, tolerance of Islam through sufism has been widely accepted since the spread of islam at an early stage. Secondly, the interaction between Sufism and sharia is not contradictory where the application of sharia can be explained easily by using sufism methodology.